(untitled) (European Journal of Pure and Applied Mathematics, 2024)
The current manuscript aims to present an efficient numerical technique for solving third-order reaction-diffusion singularly perturbed boundary-value problems. The method is based on coupling the restarted Adomian decomposition method and the shooting method. The study further provided a complete outline of the coupled numerical method and used it in tackling the governing class of third-order differential equations. The efficacy of the proposed method is demonstrated on test problems. Lastly, a high level of exactitude between the obtained approximate solution and the exact solution is achieved through comparison tables and figures.